The relationship of education and ICT determinants on nation's growth: an empirical analysis of Malaysia and muslim countries - Sayed Kushairi, Sayed Nordin; Bushra, Abdul Halim; Mohd Zamzuri, Ab Rashid; Mohd Shahrizan, Othman (Universiti Teknikal Malaysia Melaka, 2014)
Human capital is an important input to growth almost in every economy. This paper analyses and compares the contribution of education and ICT(information and communication Technology) variables on economic growth. Multiple regression and unbalanced panel approach are applied to a sample of ten countries from 1976 to 2010. The results revealed that school life expectancy, primary and secondary school enrolment influence on Malaysia’s growth. Meanwhile, the number of internet users, primary and tertiary school enrolment influences growth of Muslim countries.